GAMBARAN UPAYA PENEGAHAN LOW BACK PAIN PADA PERAWAT - Novitasari Wijayanti Silalahi; Erwin Erwin; Gamya Tri Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Low back pain is an uncomfortable condition on the lower back accompanied by limitation of activity and pain when moving or mobilizing. One of the professions that has a high risk of experiencing low back pain is nurses. This is related to ergonomic activities of nurses in hospitals. This study aims to describe the the efforts of low back pain prevention in nurses. This study uses descriptive quantitative design and was conducted in Selasih Hospital, Pangkalan Kerinci. The sample were 53 respondents of nurses that were taken by stratified random sampling technique. Analysis in this study used univariate analysis. The instrument in the study is a questionnaire based on back injury prevention by Kansas State University Research and Extension. The results showed that in the application of safe patient handling, majority of the respondents often applied (75.5%), in the application of assistive devices utilization, majority of the respondents often applied (84.9%), in the application of correct standing posture, majority of the respondents often applied (75.5%), in the application of the correct sitting posture, majority of the respondents rarely applied (52.8%), in the application of the correct sleeping posture, majority of the respondents often applied (54.7%) and in the application of stretching exercises, majority of the respondents often applied (66.0%). It could be concluded that efforts to prevent low back pain in nurses are often applied.Keywords: low back pain, nurses, prevention, effortLow back pain is an uncomfortable condition on the lower back accompanied by limitation of activity and pain when moving or mobilizing. One of the professions that has a high risk of experiencing low back pain is nurses. This is related to ergonomic activities of nurses in hospitals. This study aims to describe the the efforts of low back pain prevention in nurses. This study uses descriptive quantitative design and was conducted in Selasih Hospital, Pangkalan Kerinci. The sample were 53 respondents of nurses that were taken by stratified random sampling technique. Analysis in this study used univariate analysis. The instrument in the study is a questionnaire based on back injury prevention by Kansas State University Research and Extension. The results showed that in the application of safe patient handling, majority of the respondents often applied (75.5%), in the application of assistive devices utilization, majority of the respondents often applied (84.9%), in the application of correct standing posture, majority of the respondents often applied (75.5%), in the application of the correct sitting posture, majority of the respondents rarely applied (52.8%), in the application of the correct sleeping posture, majority of the respondents often applied (54.7%) and in the application of stretching exercises, majority of the respondents often applied (66.0%). It could be concluded that efforts to prevent low back pain in nurses are often applied.Keywords: low back pain, nurses, prevention, effort